2015
DOI: 10.1113/jphysiol.2014.270101
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol protects against doxorubicin‐induced cardiotoxicity in aged hearts through the SIRT1‐USP7 axis

Abstract: Key pointsr Doxorubicin induced functional deteriorations and elevations of USP7-related apoptotic/catabolic signalling in the senescent heart r Resveratrol protects against doxorubicin-induced alterations through the restoration of SIRT1 deacetylase activity Abstract A compromised cardiac function is often seen in elderly cancer patients receiving doxorubicin therapy. The present study tested the hypothesis that acute intervention with resveratrol, a natural anti-oxidant found in grapes and red wine, reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 37 publications
2
54
0
Order By: Relevance
“…These results suggest a SIRT1-independent effect of resveratrol, and in fact treatment of infected mice with resveratrol plus EX527, an specific SIRT1 inhibitor used as previously described [37], was not able to reverse the significant benefits of resveratrol on ECG abnormalities (S7 Fig). Together, these data support the notion that AMPK, but not SIRT1, is activated in response to resveratrol in CCC.…”
Section: Resultsmentioning
confidence: 56%
“…These results suggest a SIRT1-independent effect of resveratrol, and in fact treatment of infected mice with resveratrol plus EX527, an specific SIRT1 inhibitor used as previously described [37], was not able to reverse the significant benefits of resveratrol on ECG abnormalities (S7 Fig). Together, these data support the notion that AMPK, but not SIRT1, is activated in response to resveratrol in CCC.…”
Section: Resultsmentioning
confidence: 56%
“…Additionally, resveratrol, a SIRT 1 activator, is known to possess many beneficial biological activities. For instance, resveratrol can ameliorate doxorubicin-induced cardiotoxicity in aged hearts through restoring the SIRT1 activity, thus attenuating the USP7-related catabolic/ pro-apoptotic signaling [42]. Consequently, it can be easily speculated that TQ may exert its cardioprotective effect through activation of the SIRT 1 signaling pathway.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%
“…Taken together, it is concluded that HO‐1 plays a core role for protective action of resveratrol in doxorubicin‐induced cardiomyocytes apoptosis . Furthermore, it has been reported that resveratrol ameliorates doxorubicin‐induced apoptosis in cardiomyocytes through the restoration of SIRT1 activity, which decreases the level of acetylated p53 and p53‐dependent transcription of Bax .…”
Section: Resveratrol Mitigates Cardiomyocytes Apoptosis Induced By Domentioning
confidence: 80%
“…Interestingly, the use of resveratrol in combination with doxorubicin has been reported to prevent doxorubicin‐induced cardiotoxicity as well as to exert a synergistic effect against tumour cells both in vivo and in vitro . It is noteworthy that the cardioprotective effect of resveratrol is associated with reduced oxidative stress, inhibited apoptosis and modulated autophagy process . This article discusses the protective effect of resveratrol in doxorubicin‐induced cardiotoxicity.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation